Pengaruh Fraud Hexagon Terhadap Kecurangan Laporan Keuangan: Studi Empiris Perusahaan Sektor Finansial Non Bank yang Terdaftar di Bursa Efek Indonesia Tahun Periode 2021-2023 - Rishnu Andi; Fauzan (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to analyze the effect of Fraud Hexagon on financial statement fraud in non-bank financial sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2021-2023. This study uses a quantitative method with secondary data from the company's annual report. The sample was determined using a purposive sampling technique based on certain criteria. The dependent variable in this study is financial statement fraud as measured by the F-Score, while the independent variables consist of stimulus, capability, opportunity, rationalization, ego, and collusion. The data were analyzed using multiple linear regression with SPSS software. The results showed that stimulus, opportunity, and ego had an effect on financial statement fraud, while capability, rationalization, and collusion had no effect. These results indicate that financial pressure, opportunities in the industry, and CEO ego characteristics can increase the risk of financial statement manipulation. Therefore, companies need to strengthen supervision and regulation to reduce the risk of fraud, especially in conditions of financial instability and weak governance.